Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1034/j.1600-0609.2002.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic hypermutation and VH gene usage in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is considered to derive from naïve, pregerminal center (GC) CD5+ B-cells. However, the cell of origin has been questioned in recent studies that showed somatic hypermutations in the immunoglobulin (Ig) variable heavy chain (V(H)) genes in subsets of MCL. To clarify this issue, we analyzed the IgV(H) genes for the presence of somatic hypermutations in 51 MCL cases. Twenty percent of the MCL cases displayed somatically mutated V(H) genes (defined as >2% mutated), whereas 80% showed unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 47 publications
(79 reference statements)
6
69
0
7
Order By: Relevance
“…18 Similarly, Pittaluga et al 19 21 Compared to these studies, we found a higher percentage (60%) of mutated cases. This discrepancy may be due to our referral patient population or to the relatively small size of our series, rather than reflecting the biology of MCL cases that subsequently undergo histologic progression.…”
Section: Discussionsupporting
confidence: 45%
“…18 Similarly, Pittaluga et al 19 21 Compared to these studies, we found a higher percentage (60%) of mutated cases. This discrepancy may be due to our referral patient population or to the relatively small size of our series, rather than reflecting the biology of MCL cases that subsequently undergo histologic progression.…”
Section: Discussionsupporting
confidence: 45%
“…20 Several studies have reported the presence of somatic mutations in a subset of MCL. 12,[21][22][23][24][25] Although none of the studies reports a statistically different survival advantage for mutated cases, a study by Orchard et al, 12 demonstrates that t (11;14) lymphocytosis is also heterogeneous with respect to IgV H mutations, with the presence of somatic mutations being restricted to the non-nodal group, and more frequently found among the long-term survivors.…”
Section: Introductionmentioning
confidence: 99%
“…High-molecular-weight DNA was prepared from fresh frozen tumor tissues using a standard protocol for phenol-chloroform extraction as previously outlined 2 or with the QIAamp DNA Mini Kit (Qiagen, Valencia, CA, USA), according to the recommendations from the manufacturer.…”
Section: Cghmentioning
confidence: 99%
“…For the majority of cases, naïve pregerminal center B cells, located in primary lymphoid follicles or the mantle zone of secondary follicles are considered to give rise to the transformed cells. 1,2 Cytogenetically, mantle cell lymphoma is characterized by a reciprocal translocation, t(11;14)(q13;q32), which is found in virtually all cases. 3 Through this rearrangement, CCND1/PRAD-1/BCL1 on chromosome 11 is juxtaposed to the active IGH enhancer on chromosome 14.…”
mentioning
confidence: 99%
See 1 more Smart Citation